EMERGING THE SCO AS AN EFFECTIVE UNION IN ASIA: CHINA’S ROLE AND AMBITIONS - Enayatollah Yazdani; Rizwan Hossain (Faculty of Social and Political Sciences University of Bangka Belitung, 2020)
The Shanghai Cooperation Organization (SCO)is an Eurasianpolitical, economic and security alliance.The SCO which itsoriginal focus was on border disputes, has begun anevolution, changing its focus to to economic cooperation andissues of counter terrorism and regional security. China as afounder member of the SCO has an evolving role in theorganization. This paper aims to address this main question:what is the position and role of China in the SCO? The paperdiscusses that China as a major power with a growingeconomy is playing an effective role in the organization. Andthe goals which China pursues in this organization are in linewith the larger goals of the country in the internationalarena.